You were always mine - Pride, Christine; Piazza, Jo (Atria Books, 2023)
Cinnamon Haynes has fought hard for a life she never thought was possible--a good man by her side, a steady job as a career counselor at a local community college, and a cozy house in a quaint little beach town. It may not look like much, but it's more than she ever dreamed of or what her difficult childhood promised. Her life's mantra is to be good, quiet, grateful. Until something shifts and Cinnamon is suddenly haunted by a terrifying question: "Is this all there is?" Daisy Dunlap has had her own share of problems in her nineteen years on earth--she also has her own big dreams for a life that's barely begun. Her hopes for her future are threatened when she gets unexpectedly pregnant. Desperate, broke, and alone, she hides this development from everyone close to her and then makes a drastic decision with devastating consequences. Daisy isn't the only one with something to hide. When Cinnamon finds an abandoned baby in a park and takes the blonde-haired, blue-eyed newborn into her home, the ripple effects of this decision risk exposing the truth about Cinnamon's own past, which she's gone to great pains to portray as idyllic to everyone...even herself. As Cinnamon struggles to contain old demons, navigate the fault lines that erupt in her marriage, and deal with the shocking judgments from friends and strangers alike about why a woman like her has a baby like this, her one goal is to do right by the child she grows more attached to with each passing day. It's the exact same conviction that drives Daisy as she tries to outrun her heartache and reckon with her choices. These two women, unlikely friends and kindred spirits must face down their secrets and trauma and unite for the sake of the baby they both love in their own unique way when Daisy's grandparents, who would rather die than see one of their own raised by a Black woman, threaten to take custody." --